Risk factors for acute gastrointestinal bleeding following myocardial infarction in veteran patients who are prescribed clopidogrel. Issue 4 (April 2014) - Cuschieri, Justin R; Drawz, Paul; Falck‐Ytter, Yngve; Wong, Richard C K
<x xml:space="preserve">Abstract</x> Objective Our aim was to identify risk factors for acute gastrointestinal (GI) bleeding in patients with myocardial infarction (MI) who were prescribed clopidogrel following hospital discharge. Methods Data were collected retrospectively from patients treated in Veteran Affairs hospitals in Ohio, USA, from 2001 to 2008 with a primary diagnosis of MI (International Classification of Diseases, 9th Revision) and a prescription for clopidogrel filled within 48 h of discharge. Primary outcome was acute GI bleeding after discharge. Results Acute GI bleeding occurred in 107 of 3218 patients. Bleeding occurred in those who were elder (66.2 vs 62.4 years, P = 0.0002), had lower glomerular filtration rate (74 vs 81 mL/min, P = 0.024), had filled prescription for warfarin (15.9% vs 6.9%, P = 0.0004), diagnosed as atrial fibrillation (20.6% vs 11.1%, P = 0.003), chronic liver (5.6% vs 2.2%, P = 0.018) or kidney disease (29.0% vs 19.4%, P = 0.016). A risk model and GI bleed risk score were developed and showed that patients with age >65 years, use of warfarin, the presence of chronic liver or kidney disease were at increased risk for GI bleeding. Conclusions Veterans patients of advanced age, using warfarin and with chronic liver and kidney disease may be at increased risk of GI bleeding when prescribed clopidogrel following MI. A scoring system may help to identify patients at high risk for GI bleeding.